Validating instrument to assess science literacy and independent learning skills in high school - Bebi Ramalia Alfi; P. Paidi; Anggi Tias Pratama (JPBI (Jurnal Pendidikan Biologi Indonesia))
Inadequate science literacy and independent learning hinder students' ability to analyze scientific information. This study aimed to develop and validate a measurement instrument to assess science literacy and independent learning skills among high school students. The instrument was piloted with 20 twelfth-grade students at SMAN 03 Kota Yogyakarta to assess its reliability and validity. The validated instrument was administered to 20 eleventh-grade students at the same school to identify the profiles of these two skills and explore their relationship in the context of the nervous system. The validity analysis demonstrated that both the science literacy and independent learning instruments exhibited strong validity. Pearson correlation analysis revealed that 20 items in the independent learning questionnaire were strongly correlated with the total score. Rasch analysis of the science literacy test indicated low infit mean square values, appropriate p-values, and high point biserial values, suggesting well-functioning items. Cronbach's alpha reliability coefficients for both instruments were excellent. The profile analysis revealed a discrepancy, with many students showing high independent learning levels but low science literacy scores on the nervous system topic. This gap suggests that even students capable of independent learning may face challenges in grasping specific scientific concepts.